Bridging the Attitude-Behavior Gap in Green Consumption: A Systematic Literature Review and Integrative Framework - Indra Permadi; Arissetyanto Nugroho; Sri Widyastuti (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
The persistent attitude-behavior gap represents one of the most significant challenges in sustainable consumption research. Despite growing environmental consciousness, consumers frequently fail to translate their pro-environmental attitudes into actual green purchase behavior. This systematic literature review synthesizes existing research on the mechanisms that bridge or widen this gap, with particular focus on the dual psychological pathways of value perception and trust formation. Following PRISMA 2020 guidelines, this study systematically reviews empirical articles published between 2016-2025 from Scopus and Web of Science databases. The Theory-Context-Characteristics-Methodology (TCCM) framework is employed to organize and synthesize findings, identify research gaps, and propose future research directions. The review reveals that the Theory of Planned Behavior and Value-Belief-Norm Theory dominate the theoretical landscape, while Signaling Theory remains underutilized. Green perceived value and green trust emerge as critical mediating mechanisms, with the value-based pathway demonstrating stronger effects in emerging market contexts. Environmental concern functions as a significant boundary condition that strengthens the translation of psychological antecedents into actual behavior. This study contributes by integrating fragmented findings through comprehensive TCCM analysis, proposing an integrative dual-pathway framework, and providing a structured research agenda. The review advances theoretical understanding of how environmental signals are processed through cognitive and affective mechanisms to influence consumer behavior.